Transfusion effect of random donor platelet and single donor platelet in thrombocytopenic patients at tertiary care hospital of South Gujarat - Unagar, Chirag A.; Patel, Snehal G.; Patel, Kamal A.; Pandya, Amrish N.; Jarag, Mayur A.; Patel, Jitendra N.; Wadhwani, Sangita J. (International Journal of Research in Medical Sciences, 2017)
Background: Platelet transfusion plays a key role in therapy for the patients with thrombocytopenia. Superiority of Single donor platelet (SDP) over Random donor platelet (RDP) transfusions is largely assumed, but unproven. Platelet Rich Plasma-Platelet concentrate (PRP-PC) and Apheresis-PC were prepared and their therapeutic efficacy were assessed in thrombocytopenic patients. Methods: This study included 60 transfusion episodes consisting of 30 SDP and 30 RDP (147units of RDP). The post transfusion efficacy of transfused platelets was assessed at 1 hour and 24 hours by corrected count increment (CCI) and percentage recovery (PR). Paired ‘t’-test was used for statistical analysis and a probability of p<0.05 was used to reject null hypothesis. Results: The mean platelet dose of SDP (n=30) and RDP (n=30) was 2.86±1.05 x 1011 and 2.36±0.54 x 1011 respectively. The mean platelet increments of SDP at 1 hour and 24 hours were 38±18.1 x 103/μl and 37.3±20.7x 103/μl. The mean platelet increments of RDP at 1 hour and 24 hours were 28.5±11.4 x 103/μl and 26 ±11.6 x 103/μl. The mean CCI of SDP at 1hour and 24 hours were 21.4 ±7.3 x 103/μl and 20.8±7.4 x 103/μl respectively. The mean CCI of RDP at 1hour and 24 hours were 18.5±6.3x 103/μl and 17.4±7.6 x 103/μl respectively. Conclusions: Post-transfusion increments were significantly higher in patients who received SDP as compared to RDP, but the CCI and PR were comparable in both groups of patients.